Comparing the effects of intrathecal and intra-articular magnesium sulfate and fentanyl on pain after knee arthroscopy; double-blind clinical trial - Houriye Safaripoor; Hesameddin Modir; Alireza Susanabadi; Seyed Yosef Shahtaheri; Mohsen Parsi Khamene (The Indian Anaesthetists' Forum)
Objectives: The aim of this study was to compare the effects of intrathecal and intra-articular magnesium sulfate (IA-Mg) and fentanyl on pain after knee arthroscopy (KA). Materials and Methods: This double-blind clinical trial was conducted in 2022–2023. One hundred and forty candidates for KA were randomly allocated to four groups, namely intrathecal magnesium sulfate, IA-Mg, intrathecal fentanyl (IT-F), and intra-articular fentanyl. A medical intern used a 0–10 visual analog scale to assess participants’ post-KA pain at recovery and 1, 4, 6, 12, and 24 h after KA. Participants with a pain score of more than 4 were provided with intravenous pethidine 25 mg. Data were analyzed at a significance level of < 0.05 and using the SPSS software (version 22.0). Results: No significant difference was found among the groups respecting participants’ arterial oxygen saturation, heart rate, blood pressure, and KA duration (P > 0.05). The mean score of pain significantly increased in all study groups (P < 0.05) and the mean score of pain in the IA-Mg group was significantly less than the other groups (P = 0.001). Respecting postoperative complications, only six cases from the IT-F group experienced pruritus (P = 0.001). Conclusion: IA-Mg can significantly reduce post-KA pain and the need for postoperative analgesics. Therefore, it may be a safe and effective adjacent therapy for post-KA pain management.